Suppressive Effects of Clerodendrum volubile P Beauv. [Labiatae] Methanolic Extract and Its Fractions on Type 2 Diabetes and Its Complications - Erukainure, Ochuko L.; Hafizur, Rahman M.; Kabir, Nurul; Choudhary, M. Iqbal; Atolani, Olubunmi; Banerjee, Priyanka; Preissner, Robert; Chukwuma, Chika I.; Muhammad, Aliyu; Amonsou, Eric O.; Islam, Md. Shahidul (Frontiers Media, 2018)
Type 2 diabetes is the most prominent of all diabetes types, contributing to global morbidity and mortality. Availability and cost of treatment with little or no side effect especially in developing countries, remains a huge burden. This has led to the search of affordable alternative therapies especially from medicinal plants. In this study, the antidiabetic effect of the methanolic extract, dichloromethane (DCM), butanol (BuOH) and aqueous fractions of Clerodendrum volubile leaves were investigated in type 2 diabetic rats for their effect on glucose homeostasis, serum insulin level and hepatic biomarkers, lipid profile, pancreatic redox balance and Ca2+ levels, and β-cell distribution and function. The DCM was further fractionated to isolate the active compounds, biochanin and 5,7,4'-trimethoxykaempferol. They were investigated for their toxicity and ADMET properties, a-glucosidase and angiotensin I converting enzyme (ACE) inhibitory activities in silico. There were significant (p < 0.05) decrease in blood glucose, cholesterol, LDL-C, vLDL-C, triglyceride, AST and ALT levels in all treated groups, with DCM fraction showing the best activity. All treated rats showed significantly (p < 0.05) improved anti-oxidative activities. Treatment with the DCM fraction led to significant (p < 0.05) increased serum insulin and pancreatic Ca2+ levels, as well as improved β-cell distribution and function. DCM fraction also showed improved glucose tolerance. DCM fraction dose-dependently inhibited ACE activity. The toxicity class of the isolated compounds was predicted to be 5. They were also predicted to be potent inhibitors of cytochrome P (CYPs) 1A2, 2D6 and 3A4. They docked well with a-glucosidase and ACE. These results indicate the therapeutic potential of the plant against type 2 diabetes, with the DCM fraction being the most potent which may be attributed to the isolated flavones. It further suggests antihypertensive potentials of the DCM fraction. However, inhibition of CYPs by the flavones may suggest caution in usage with other prescribed drugs metabolized by these enzymes.